2003
DOI: 10.1055/s-2003-42846
|View full text |Cite
|
Sign up to set email alerts
|

Die Weil-Osteotomie bei Metatarsalgie

Abstract: It is possible with the Weil osteotomy to correct the metatarsal length accurately according to the preoperative planning. This results in the prevention of new callus formation under the neighbouring metatarsal head. Stable internal fixation allows the early mobilisation of the MTP joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
0
6
0
6
Order By: Relevance
“…It has also been described as a treatment option for patients with lesser toe deformities such as claw toes or hammer toes by relaxing tight periarticular structures. 1,2,3,8,9 While the success rate for this surgery is high, it can also have a high rate of complications. Several authors have reported "floating toes", restricted MTP motion especially extension, redislocation, persistent pain, transfer metatarsalgia, and hardware migration.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been described as a treatment option for patients with lesser toe deformities such as claw toes or hammer toes by relaxing tight periarticular structures. 1,2,3,8,9 While the success rate for this surgery is high, it can also have a high rate of complications. Several authors have reported "floating toes", restricted MTP motion especially extension, redislocation, persistent pain, transfer metatarsalgia, and hardware migration.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term results for the Weil osteotomy have been very promising. 16 Hart et al 17 reported 83% (29 of 35) excellent and 17% (6 of 35) good results at 31 months after the procedure. Trnka et al 14,23 reported 68% (21 of 31) excellent and 13% (4 of 31) good results after 30 months of follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Previously published articles mention a high rate of post-operative dorsiflexion contracture along with floating and stiff toes. 17,24 Once the MTP joint is dislocated and the plantar plate is elongated and ruptured, the dorsal capsule is already contracted in the chronically dislocated MTP joint. By using the Weil osteotomy and making the procedure as parallel as possible to the ground, shortening of the metatarsal helps to reduce the pre-operatively contracted MTP joint by releasing the dorsal contracture, the collateral ligaments and intrinsic muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…İkincil sallanma ( rocker) metatarsalji MT'lerin yükseltilmesiyle tedavi edilmelidir. [40,41] Geleneksel Weil osteotomisiyle tedavi edilen hastaların %70-100'ünde iyi ve mükemmel uzun dönem sonuçlar rapor edilmiştir. [1,4,[40][41][42][43] Cerrahi sonrası komplikasyonlar arasında, MTF eklem sertliği, yüzen başparmak deformitesi (örn: başparmak yük verirken yerle temas etmez), küçük MT başının plantara yer değiştirmesinden dolayı meydana gelen bölgesel ikincil sallanma ( rocker) metatarsalji, aşırı kısalmanın neden olduğu transfer metatarsalji (örn: yetersiz planlama), yüzeyel yara iyileşme problemleri ve kompleks bölgesel ağrı sendromudur.…”
Section: Fizik Muayeneunclassified